Production of Biogas by Rural Digesters Containing Local Household Fat and Protein-Rich Food Wastes from Gbadagbadzu, Ndawangwa and Kuchiworo communities in Lavun Local Government Area, Niger State, Nigeria - A. M. Shaba; M. E. Kolo; A. S. Mohamme; G. J. Abel; O. Amuda (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate the Production of Biogas by Rural Digesters Containing Local Household Fat and Protein-Rich Food Wastes from Gbadagbadzu, Ndawangwa and Kuchiworo communities in Lavun Local Government Area, Niger State, Nigeria using appropriate standard procedures. Data obtain indicated that in 39 days detention time, rural digester RA had a biogas volume of 98.14 cm3, RB had 31.53 cm3, RC gave 6.21 cm3 while RD (control) that was without starter culture produced 4.72 cm3 within a detention time of 33 days  Thus, RA had the highest yield while the yield fluctuated in other digesters . The total volumes were 10539.39 cm3, 5426.71 cm3, 2275.93 cm3 and 124.04cm3 from rural biogas digesters RA, RB, RC and RD respectively.   The highest frequency of occurrence was recorded with Bacillus cereus (35.48%) while Bacillus licheniformis had the least frequency of occurrence (2.65%). Clostridium perfringens, Sphingobacterium yamdrokense, Alkaligenes feacalis, Pseudomonas aeruginosa, Methanosarcina barkeri, Staphylococcus epidermidis and Salmonella enterica had 6.19%, 15.04%, 15.30%, 5.30%, 7.96%, 5.30% and 6.19% respectively. The results also revealed that rural digester RA had the highest total number of isolates and decreased in the descending order from RA (50) to RB (32), RC (19) and to RD (12) with Bacillus cereus, Alkaligenes feacalis and Methanosarcina barkeri found in all the digesters.  The daily temperature of the digesters varied between 28.0 0C and 32.0 0C throughout the fermentation period, with the average temperature ranging between 29.41 0C and 30.7 0C. Also, temperature increased gradually to the peak leading to increase in biogas volume. When the temperature was 28 oC, samples from community A produced biogas yield of 1.00 cm3, B gave 3.0 cm3, C produced 3.0 cm3 while D generated 0.0 cm3. But at a temperature of 32 oC, wastes from community A yielded 25.0 cm3, B yielded 32.10 cm3, C produced 29.0 cm3 while D (control) yielded 12.09 cm3..This implies that household wastes could serve as suitable substrates for biogas production and that the utilization of these substrates for biogas production could solve their disposable problems, thus, making way for abundant source of sustainable energy. Biogas should be preferably produced from household wastes because it is cheap. Besides; this will go a long way to reduce the demand for wood from the forest and the impact of greenhouse gas emission in Nigeria.